2020
DOI: 10.1111/jonm.13017
|View full text |Cite
|
Sign up to set email alerts
|

British South Asian male nurses' views on the barriers and enablers to entering and progressing in nursing careers

Abstract: Aim:To ascertain British South Asian male nurses' views on the barriers and enablers to entering and progressing in nursing education and careers.Background: There is a shortage of men from Black, Asian and Minority Ethnic groups in the National Health Service nursing workforce. There is a dearth of evidence on the views of British south Asian men on this subject. Methods:A qualitative interpretative intersectional approach was used to carry out one-to-one interviews (n = 5) with British South Asian male nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 79 publications
1
20
0
Order By: Relevance
“…Sri Lanka's nurses perceived nursing as women's work and a stereotypically 'feminine' profession as found in most other contexts (Cottingham, 2015;Gray, 2010;Qureshi et al, 2020). Confirming prior research (Cottingham, 2015;Simpson, 2004Simpson, , 2007, this study revealed that allocation of job roles and clinical areas were gendered where female nurses handled stereotypically 'feminine' maternity or paediatric wards while male nurses handled stereotypically 'masculine' psychiatric or medical wards.…”
Section: Discussionsupporting
confidence: 75%
“…Sri Lanka's nurses perceived nursing as women's work and a stereotypically 'feminine' profession as found in most other contexts (Cottingham, 2015;Gray, 2010;Qureshi et al, 2020). Confirming prior research (Cottingham, 2015;Simpson, 2004Simpson, , 2007, this study revealed that allocation of job roles and clinical areas were gendered where female nurses handled stereotypically 'feminine' maternity or paediatric wards while male nurses handled stereotypically 'masculine' psychiatric or medical wards.…”
Section: Discussionsupporting
confidence: 75%
“…One of the main explanatory factors of these observed deferential are linked by several authors to 'white hierarchy' and the 'ruling relations' between senior teams and other workers as well as institutional and structural racism where unspoken rules favour white and male professional staff for better jobs (Howells et al, 2018;;Sahraoui, 2019;Milner et al, 2020;Qureshi et al, 2020). Furthermore, several authors argued that ME workers internalise such structures within this construct, not seeing themselves 'fitting in' among the 'white crowed' senior colleagues and lack a role model in senior positions (Qureshi et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…All staff included in these data were equally likely to experience harassment or bullying from patients (Kline et al, 2017). However, other studies indicated that ME healthcare staff, including students in placements, were subjected to more bullying and harassment incidents from patients (Birks et al, 2017;Howells et al, 2018;Qureshi et al, 2020). An international comparative study, focusing on nursing students in Australia and the UK, shows higher reported bullying rates among male students in the UK (Birks et al, 2017).…”
Section: Harassment and Bullying In The Workplacementioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, within the current image and discourse in nursing, not only have minority ethnic people and men been excluded or marginalised, men from minority ethnic backgrounds have been particularly invisible (35). For instance, recent investigations into the experiences of minority ethnic male nurses emphasise the views of these nurses feeling twice invisible as they are neither White nor female (35).…”
Section: Ethnic Minority Nurses and The Media: Whitewashing The Truthmentioning
confidence: 99%